University student’s perceptions about climate change: the case of interior design and architecture students of a brazilian university - Alves, Fátima (2020)
Higher Education Institutions have a very important educational role to play in the formation of active citizens involved in climate change mitigation and/or adaptation. Few studies assess higher education students’ knowledge and attitudes about this issue, and the contribution of their graduate course to the deepening of this knowledge and to the change of attitudes and behaviours. This study aims to contribute to this gap and to provide reflection and data on the views, attitudes and behaviours about climate change issues, of graduate students of Interior Design and Architecture of University of Amazonia, Brazil. We surveyed university students from two graduation programs targeting their knowledge, attitudes and behaviour on climate change, and their views of the role that their graduate degree had on it. Further research is necessary so that curricula programs can be adequate to promote better knowledge and attitudes about climate change and an active engagement of future participative professionals and citizens, in order to cope with the environmental crises and climate change challenges and to be part of the solution for climate change problems.